The degree of patient satisfaction with diltiazem gel in the treatment of anal fissures. Issue 2 (12th March 2012) - Alves, M. Lobo; Ribeiro, N.; Alves, S.; Neves, C.; Falcão, F.
Abstract : Background: Anal fissure is a common and painful condition that often affects young adults of both sexes. Topical 2% diltiazem gel is described as an effective first-line treatment for chronic fissure with an optimised toxicity profile. When it became unavailable on the Portuguese market, our hospital and the Faculty of Pharmacy from Lisbon University developed a formulation and are producing and dispensing it. Purpose: To assess the degree of patient satisfaction with the use of diltiazem gel in anal fissure. Materials and methods: Cross-sectional descriptive study with information collected at a single moment in time through a telephone interview. Results: All patients to whom the Pharmacy Department dispensed diltiazem gel between January and July 2011 were included. Number of patients was 137 (68 females, 69 males); mean age: 50.3 years. 70 patients answered the questionnaire (52 were excluded). The majority had higher education (baccalaureate or a degree). Regarding health status evolution, pain improved or improved considerably in 77% of patients. With regard to bleeding, it improved a lot or completely in 63% patients. As for itching and/or perianal irritation, it improved or improved considerably in 41% patients (33% didn't know). As for passing faeces, in 14% patients it greatly improved or improved completely (77% didn't know). Concerning side effects, only 2 patients had headaches and 1 mentioned dizziness. In terms of degree of satisfaction with the gel, 17% were completely satisfied, 57% very satisfied, 17% at least somewhat satisfied, 4% somewhat satisfied, 1% completely unsatisfied and 3% didn't know. Of the 70 patients, 56% considered themselves cured, not cured 39% and 6% didn't know. Conclusions: Diltiazem gel seems to be a good alternative for treating anal fissure. The production of medicines by pharmacy departments is very important for meeting patients' needs not met by the pharmaceutical industry.